Cryptocurrencies and Blockchain: Potential Applications in Government and Business. Issue 1 (4th May 2022) - Pestunov, A.I.
ABSTRACT: Cryptocurrencies and distributed registers (blockchains) have recently attracted increased interest among specialists from the widest variety of fields. In turn, the public has generated a pool of regularly asked questions, which have not yet been answered thoroughly. This article provides lines of reasoning with regard to several popular questions linked to this subject. It also addresses issues such as the creation of national cryptocurrencies and use of blockchain technology by businesses and governments. In addition, it analyzes the opinion that cryptocurrencies are a financial pyramid. Finally, it briefly examines the configuration of Bitcoin's distributed register and looks at how this register could be affected by the hypothetical creation of a quantum computer.